Do Emotional Intelligence and Academic Persistence Interrelated in Final Year Students? - Paramma, Putry Leana; Aditya, Andi Muhammad; Thalib, Tarmizi (Educational Researcher Journal, 2025)
Final students are students who often face academic pressure, final assignments, and preparations for entering the world of work. Emotional intelligence is important for dealing with stress, maintaining motivation, and having academic persistence which gives a final student the ability to continue fighting to achieve their academic goals despite facing challenges. various obstacles. For final students, challenges such as final assignments and preparation for graduation can test their level of persistence. This quantitative research aims to explain the relationship between emotional intelligence and academic persistence in final students. Data was collected using The Schutte Self Report Emotional Intelligence Test (SSEIT) scale for emotional intelligence and The academic persistence scale for academic persistence, then analysis was carried out using reliability and validity tests, assumption tests and hypothesis tests. The results of this research show that specifically emotional intelligence and academic persistence in final students have a relationship with a Correlation Coefficient of (.755), which means it has a positive relationship and a significance value of 0.000 is smaller than 0.05, for linearity it shows (628.951) for the sig F value. The significance deviation of linearity is 0.000. From the results of this research which shows its significance towards emotional intelligence and academic persistence in final students, it shows that high emotional intelligence is associated with stronger academic persistence. Overall, research on the relationship between emotional intelligence and academic persistence can yield a variety of beneficial implications in improving college students' academic success, supporting their well-being, and preparing them for future challenges.